Plant geometry and nitrogen effect on fatty acid composition of sesame (Sesamum indicum L.) seed: Plant geometry and nitrogen effect on fatty acid composition of sesame (Sesamum indicum L.) seed - K RAMESH; G SURESH; M A A QURESHI; P RATNAKUMAR; PRADUMAN YADAV; CH V HARIPRIYA (Journal of Oilseeds Research, 2020)
A field experiment was conducted to determine the effect of fertiliser N on seed fatty acid composition (palmitic, stearic, oleic and linoleic acid content) of sesame. Nitrogen (N) application had a profound effect on the fatty acid composition. An increase in N application from 0 to 45 kg/ha increased linoleic acid but reduced oleic acid and palmitic acid contents.